Working Capital Management and Its Impact on the Profitability of Pukar International Co.Ltd. - Ojha, Puspa Raj (NCC Journal, 2019)
This paper aims to report the results of an investigation of the relative importance of working capital management, measured by the Return on Assets (ROA), and its components (Current ratio, average collection period and average payment period) to the profitability of Pukar International Trading. This paper analyzes the effect of working capital Management on firm’s profitability in Nepal for the period 2071 to 2072. For this Purpose, financial data of four year is used. Pearson’s correlation and Descriptive analysis were used to establish the relationship between working capital management and firm’s profitability and components of working capital like Average collection period, Average payment period and Current ratio. The study finds a negative relationship between profitability and average collection period and average payment period, but appositive relationship between profitability and current ratio. Moreover, current ratio and firm size also have significant effects on the firm’s profitability. Based on the key findings from this study it had been concluded that the management of a firm could create value for their shareholders by reducing the number of day’s accounts collection. Firms could also take long to pay their creditors in as far as they did not worry their relationships with these creditors.